Application of Spectral Phototherapy in the Treatment of Patients with Ronchopathy and Obstructive Sleep Apnea Syndrome: a Prospective Study - Bair A. Zhigzhitov; Larisa A. Marchenkova; Vladimir B. Knyazkov; Daria D. Lebedeva; Lev G. Agasarov (Вестник восстановительной медицины)
INTRODUCTION. The clinically frequently detected combination of ronchopathy (snoring) and obstructive sleep apnea is an important problem in modern medicine. Correction of this pathology is performed surgically with known success, however, in this regard, it is necessary to point out the features of the condition of most patients that prevent surgical intervention, as well as the observed frequency of recurrence of the process. In addition, the importance of transient factors in upper respiratory tract obstruction, which require correction during the acute phase, indicates the prospects for the development of modern therapeutic approaches.